The Association Between Food Insecurity and Intimate Partner Violence Among U.S. Army Soldiers - Beymer, Matthew R. (Journal of interpersonal violence, 2025)
Food insecurity in the military ranges between 25% and 33%, significantly higher than the 10.5% for civilians reported by the U.S. Department of Agriculture. The primary objective of this study is to analyze the association between food insecurity and intimate partner violence (IPV) victimization among U.S. Army Soldiers. The secondary objective is to determine if there are any moderating effects in the relationship between food insecurity and IPV victimization by demographic, financial, and mental health covariates. A cross-sectional, online survey was administered by the U.S. Army Public Health Center at an Army installation in 2019; 56% of respondents reported that they were married or in a relationship (n = 2,740). The main predictor was the two-item food insecurity screener (Hunger Vital Signs), which measures marginal food insecurity (encompassing marginal, low, and very low food security). The main outcome was IPV victimization as measured by the Hurt, Insult, Threaten, Scream scale. Multiple logistic regression was used to assess the association between marginal food insecurity and IPV victimization, controlling for demographic, financial, and mental health covariates. In a multivariable model, marginally food insecure respondents had 2.05-fold greater adjusted odds of reporting any IPV victimization when compared to highly food secure respondents (95% confidence interval [1.40, 3.00]). The only interaction that was statistically significant was between anxiety and food insecurity on IPV victimization (p = .0034). Interactions by soldier’s military rank, birth sex, and race and ethnicity were not statistically significant. IPV has implications for the emotional and physical health of survivors. In addition, service members who are food insecure may experience similar decrements in emotional and physical health due to suboptimal nutrient intake. By addressing both food insecurity and IPV, the military has the potential to increase the overall well-being of its service members and their dependents.